1998
DOI: 10.1006/jmsc.1997.0263
|View full text |Cite
|
Sign up to set email alerts
|

Importance of discarded blue whiting (Micromesistius poutassou) in the diet of lesser spotted dogfish (Scyliorhinus canicula) in the Cantabrian Sea

Abstract: N. 1998. Importance of discarded blue whiting (Micromesistius poutassou) in the diet of lesser spotted dogfish (Scyliorhinus canicula) in the Cantabrian Sea. -ICES Journal of Marine Science, 55: 331-341.The blue whiting is the most important demersal species caught by the Spanish trawler fleet in the southern Bay of Biscay. Lesser spotted dogfish are not a commercial by-catch, and are discarded immediately after sorting. During 1994 the contents of 1094 dogfish stomachs were analysed. The results show that les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 9 publications
1
64
1
1
Order By: Relevance
“…The diversity of taxa in the diet of the lesser-spotted catshark confirms that it is an opportunistic feeder irrespective of length-class, but especially so ≥30 cm TL (Lyle, 1983;Olaso et al, 1998). The diet of blackmouth catshark was less diverse than that of the lesser-spotted catshark.…”
Section: Diets Of Lesser-spotted Catshark and Blackmouth Catsharkmentioning
confidence: 68%
See 2 more Smart Citations
“…The diversity of taxa in the diet of the lesser-spotted catshark confirms that it is an opportunistic feeder irrespective of length-class, but especially so ≥30 cm TL (Lyle, 1983;Olaso et al, 1998). The diet of blackmouth catshark was less diverse than that of the lesser-spotted catshark.…”
Section: Diets Of Lesser-spotted Catshark and Blackmouth Catsharkmentioning
confidence: 68%
“…Previous studies have described feeding in catshark in the Atlantic Ocean and Mediterranean Sea (Mattson, 1981; Macpherson, 1981;Lyle, 1983;Carrassón et al, 1992), as well as in the Cantabrian Sea (Olaso and Rodríguez-Marín, 1995a;Velasco et al, 1996;Olaso et al, 1998;Gutiérrez-Zabala et al, 2001). In the present study, all the available data on the feeding of lesser-spotted catshark and blackmouth catshark during the autumn have been integrated to compare their food habits and the influence of their habitats on diet.…”
Section: Diets Of Lesser-spotted Catshark and Blackmouth Catsharkmentioning
confidence: 98%
See 1 more Smart Citation
“…Research on demersal scavenger species has shown that fish tend to move towards areas disturbed by trawling (Hall et al, 1993;Kaiser and Spencer, 1994;Collins et al, 1999;Demestre et al, 2000) and that fauna discarded or damaged by the gear is an important source of food for certain species (Evans et al, 1996;Kaiser and Spencer, 1994Kaiser and Ramsay, 1997;Olaso et al, 1998;. For instance, lesser weevers Echiichthys vipera are attracted by aggregations of scavenging shrimps and gobiids that constitute their natural prey (Lindeboom and De Groot, 1998), as well as pelagic portunid crabs that only appear after trawling (Wassenberg and Hill, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…13,971 tons in 1994), some 24% of which is blue whiting Micromesistius poutassou, according to Pérez et al (1996) one of the main species discarded by trawlers in the Cantabrian Sea. In the same area, Olaso et al (1998) investigated the importance of discarded M. poutassou in the diet of lesser-spotted dogfish, Scyliorhinus canicula; it represented a high percentage of the diet. As discards constitute an important food source for some demersal species, the current experiment was carried out to determine which species of fish benefit from discards as a food source and what is the effect of the discards on their feeding intensity and dietary composition.…”
mentioning
confidence: 99%